(untitled) - Patterson, David A. (New York, 2005)
This is a revision of the classic introduction to the field for all computer scientists and engineers. It includes improved examples of current architectures and updated pipelining and memory chapters to address modern processors.
Keywords: Computer organization,Computer engineering